Assessment on the relationship between housing design and Malay culture pertaining to privacy, community intimacy, segregation and hospitality - Abdul Rahim, Zaiton (2016)
Housing in Malaysia has undergone many changes influenced by colonization, modernization and urbanization. The result of urban migration in the 1970s due to the New Economic Policy has resulted in the introduction of mass housing which changed the housing scene in Malaysia especially in the urban areas. The housing design in the urban areas was influenced by Western philosophy and the need to maximize the number of increasing urban population. This study assesses the perception, translation and aspects of Malay culture pertaining to privacy, community intimacy, segregation and hospitality in the context of housing in urban areas as well as the satisfaction of Malay families on the housing design in relation to the Malay cultural aspects. Survey interview was employed involving 432 respondents living in three different housing typologies in Kuala Lumpur. Findings indicate that the traditional Malay cultural aspects are still considered as important among the urban Malays but the importance is diminishing except for privacy which is given more importance. However, behavioral regulation consistent with the traditional culture provide the level of privacy required.